Physiology of the respiratory system - Abdul Rahim, Roslina (IIUM Press, 2018)
This book aims to give a comprehensive overview on ‘Physiology of the Respiratory System’. It describes the physiological function of the respiratory system which includes mechanics of breathing, lung function test and its interpretation, exchange and transport of gases, ventilation/perfusion in the lungs, regulation of respiration, hypoxia and acclimatization to higher and lower altitude in our human body. Students are guided by the learning outcome specified for each subtopic, as they read through each chapter. This book is written in a way that it is simple and easy for the students to understand. All illustrations are specially hand drawn and colored to explain the main ideas discussed in each chapter. This handy textbook can be used as reference book in the classroom and also during the practical session.